Adipositas athletica: a group of neglected conditions associated with medical risks - Berglund, L.; Sundgot-Borgen, J.; Berglund, B. (Scandinavian Journal of Medicine & Science in Sports, 2011)
At the 2008 Olympics, the body weight of the athletes varied from 28 to 181 kg and many Olympic athletes therefore today have a stature far from the ancient Greek athletic ideals. Athletes and sports associated with leanness and their medical problems have been researched extensively. However, there has been less focus on those athletes, who may gain a competitive advantage by having excess body fat, being large or oversized. The present review introduces for the first time the concept of Adipositas athletica and gives a description and classification of these athletes. Adipositas athletica is defined as having a higher than "athletic normal" (Greek Olympic ideals) fat mass and being an elite athlete. The condition is divided into subgroups based on the intent or non-intent to increase body fat per se. Another factor is the intent to increase body mass as well as increasing physiological factors such as strength or endurance. It is concluded that most of the sports-medicine community-physicians, researchers and nutritionists - has neglected these oversized and obese athletes, their long- and short-term morbidity and mortality, their eating problems and the use of performance-enhancing drugs. Although some data on overweight and obese athletes exist, the most remarkable finding when reviewing the literature is the paucity of data. Many unanswered questions remain and great strides remain to be made